BRONCHODILATOR AND TOCOLYTIC FEATURES OF β2-ADRENOCEPTOR AGONISTS - S. Ya. Skachilova; E. V. Shilova; V. M. Pavlov; T. N. Molostova (Разработка и регистрация лекарственных средств)
The issues (aspects) of bronchodilator and tocolytic actions of β₂-adrenoceptor agonists are reviewed. The data on short-acting and new long-acting β₂-agonists are presented. It is marked that it is necessary to use long-acting β₂-agonists and glucocorticosteroids concomitantly. Examples of clinical efficacy of locally produced β₂-adrenoceptor agonist salbutamol hemisuccinate in various dosage forms used as a bronchodilator for treatment of bronchopulmonary diseases, and also as a tocolytic for habitual noncarrying of pregnancy are given.